STRATEGI KH. HASYIM ASY’ARI DALAM MENINGKATKAN KUALITAS PENDIDIKAN MELALUI LIMA NILAI PESANTREN TEBUIRENG - Rihayatul Jannah; Syamsuddin Aly (Menara Tebuireng, 2020)
Education as a process of instilling values ​​is an important entry point to be able to create a complete human being. As we all know that education has cognitive, affective and psychomotor domains. At this time the Tebuireng Islamic Boarding School is developing an education based on the values ​​of the Pesantren which is inspired by the values ​​of Hadratus Syaikh KH. M. Hasyim Asy'ari. The five values ​​are: 1) Sincerity, 2) Honest, 3) Tasamuh, 4) Hard work, and 5) Responsibility. The problem that will be discussed is how the strategy used by KH. M. Hasyim Asy'ari in improving the quality of education through the five values ​​of the Pondok Pesantren Tebuireng. To get a complete picture of the research subject, the writer uses a qualitative research type that is literary research (library research), namely research which is the source of the data is a library in the form of journals, books, scientific magazines and various documented publications. The results showed that KH. M. Hasyim Asy'ari has special attention to the spread of education, especially education in Pondok Pesantren, because he believes that education is an important means of socializing virtue and cleansing the mind (soul), including a means to get closer for students to the pleasure of Allah Swt. According to KH. M. Hasyim Asy'ari, student ethics and teacher ethics which complement each other is a norm in the benefit of obtaining useful knowledge. Therefore, in addition to increasing his duties as an expert on Islamic education, KH. M. Hasyim Asy'ari is also a reformist figure in Islamic education in Indonesia.